Environmental Impacts of Pig and Poultry Production: Insights From a Systematic Review - Andretta, Ines; Hickmann, Felipe M. W.; Remus, Aline; Franceschi, Carolina H.; Mariani, Alexandre B.; Orso, Catiane; Kipper, Marcos; Létourneau-Montminy, Marie-Pierre; Pomar, Candido (Frontiers in Veterinary Science, 2021)
Pig and poultry production systems have reached high-performance levels over the last few decades. However, there is still room for improvement when it comes to their environmental sustainability. This aspect is particularly important because the growing demand for food must be met at an affordable cost without compromising the environment and its resources. This work presents a systematic review of studies that investigated the environmental impacts associated with pig and poultry production. Two independent searches/databases were developed, focusing on pig and poultry production systems respectively. These databases consisted of original LCA studies that assessed production systems of broiler meat, table eggs, or pork meat from the cradle-to-farm, slaughterhouse, or processor gate which estimated at least the potential effects of climate change, measured as CO2-eq. The pig database comprised 55 studies that considered a cradle-to-gate scope, starting from the production of the inputs used in agriculture up to the animal rearing phase. At the end of the evaluation procedure, 30 studies were selected to be part of the final poultry database. These studies confirmed feeding (from crop cultivation to manufacturing and transport) as the largest source of environmental impact associated with pig and poultry production systems. Several studies reported that improving feeding practices may mitigate the environmental footprint associated with both production chains. In this study, precision feeding is highlighted given its applicability to modern pig and poultry farming. This novel strategy represents a paradigm shift in animal nutrition once optimizing nutrient-use efficiency is one of the most effective tools towards more sustainable animal production systems.